Optimisation of photonic crystal weveguide based optical filter - Islam, Pratik Al; Sultan, Nameeza; Nayeem, Seefath (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.